FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KOPERASI NELAYAN DALAM UPAYA PENINGKATAN KESEJAHTERAAN ANGGOTANYA - Slamet Subari (Agriekonomika, 2012)
ABSTRACTThe fishermen cooperativeis as part of the institutional system of the local economy of coastal communities, its role is expected to make corrections to the economic injustices there. As a joint venture container for fishermen, cooperatives should be able to be "pandiga" in the system of economic institutions of fishermen communities. The objective of research was to determine the performance effect of fishermen cooperatives on the welfare of its members.The research was conducted from May to August 2010. While the location of the survey and observation were: (1) Cooperative of Makaryo Mino operating in Nusantara Fishery Port and surrounding areas in Pekalongan of Central Java, (2) Cooperative of Fishery Products Industry in the City and County of Pontianak of West Kalimantan and (3) Cooperative of Fishery and ponds in Gresik, East Java. The data were analyzed using descriptive qualitative methode.From the results of the discussion is concluded that the primary capital to the success of a cooperative to improve the welfare of its members is on the idealism and courage of acting administrators or managers to establish cooperatives. The other factors such as amenities (facilities) of effort will follow on a par with the level of development of the cooperative. Local government support is not absolute, the business experience of managers can be learned on the job, and the competitors will be able to overcome if cooperative consistent to establish competitive market system.Keywords: Fishermen cooperatives, The Welfare, The coastal communities